Kajian Numerik Penerapan Organic Rankine Cycle sebagai Metode Energi Take-Off dari Penyimpanan Energi Termal Skala Jala-Jala - Dwiyan Bagus Prayoga; Burniadi Moballa; Pranowo Sidi (Proceedings Conference on Marine Engineering and its Application, 2023)
Energy is a need that must be met in human life, if the population increases, the need for energywill also increase. A technology is needed to support human energy needs. Therefore, low temperature heatutilization is carried out using the Organic Rankine Cycle as an energy take off from a grid-scale thermalenergy storage in the form of sand media where the heat stored is heat wasted from the heat pump. After theprocess simulation is carried out, the best and feasible fluid to run the system from an ammonia heat pumpis N-Pentane with an efficiency of 7.074%. The storage medium is silica sand. The heat exchanger design onthe tube has an outer diameter of 60.3 mm for the ORC and 42.2 mm for the heat pump with an inner diameterof 54.8 mm for the ORC tube and 32.5 mm for the heat pump. The length of the heat exchanger design pipeis 165,57 m for the ORC and 479,23 m for the heat pump.